A Novel and Reusable RGO/ZnO with Nanosheets/Microparticle Composite Photocatalysts for Efficient Pollutants Degradation. Issue 30 (14th August 2018) - Zhao, Dawei; Zhou, Yi; Deng, Yuehong; Xiang, Ye; Zhang, Ya; Zhao, Zhen; Zeng, Dandan
Abstract: In this paper, we designed and synthesized a novel structure ZnO with the nanosheets grown on the surface of dumbbell‐shape ZnO via a simple hydrothermal route, and exhibits excellent photoelectrochemical performance. The reason is that nanosheets enhance charge generation, separation and transfer. Graphene as a co‐catalyst and anti‐photocorrosion material were coated on the surface of ZnO and further enhanced the photoelectrochemical properties. In process of photodegradation RhB, the experiments reveal that ZnO with 1.5 wt% RGO displayed highest rate constant of 0.0562 min −1, which is about 4 times better than pristine ZnO (heating 9 h) and several times higher than other RGO/ZnO composites. Meanwhile, the recycle experiments of 1.5 wt% RGO/ZnO suggest that it has excellent stability, reusability and excellent photocatalytic activity. The work provides a new strategy that developing nanosheets with high‐energy plane grown on the surface of semiconductor particles to enhance photoelectrochemical performance and reusability. Abstract : In this paper, we designed and synthesized a novel structure ZnO with the nanosheets grown on the surface of dumbbell‐shape ZnO via a simple hydrothermal route, and exhibits excellent photoelectrochemical performance. The nanosheets with exposed (101) crystal facet are beneficial to charges generation, separation and transfer. Meanwhile, the present work provides a novel route for fabrication self‐loaded micro and nano structure catalyst to solve the low efficiency, recover, etc.